Author Correction: Iron restriction inside macrophages regulates pulmonary host defense against Rhizopus species. Issue 1 (December 2018) - Andrianaki, Angeliki; Kyrmizi, Irene; Thanopoulou, Kalliopi; Baldin, Clara; Drakos, Elias; Soliman, Sameh; Shetty, Amol; McCracken, Carrie; Akoumianaki, Tonia; Stylianou, Kostas; Ioannou, Petros; Pontikoglou, Charalampos; et al.
The original version of this Article contained an error in the spelling of the author Emilien Etienne, which was incorrectly given as Emilien Ettiene. These errors have now been corrected in both the PDF and HTML versions of the Article.